Satellite Image Based Mapping of Wetland Tundra Landscapes Using ILWIS GIS - Polina Lemenkova (2015)
Presentation shows an application of ILWIS GIS for RS data processing with a case study of detecting land cover changes during 20-year period (1988-2011) in Yamal Peninsula, Arctic. Research goals: Distribution of different types of landscapes in the wetland tundra of the Yamal Peninsula; Monitoring changes in the landscapes of tundra; Analysis of the landscape dynamics for 2 decades (1988-2011). Data include 2 satellite images: Landsat TM for 1988 and 2011. Methods include clustering, segmentation and classification. Technical approach: Landsat TM data processing by ILWIS GIS. Methods: Supervised classification of Landsat TM images. Results demonstrated changes in selected land cover types. Study area: tundra landscapes in the wetlands of the Yamal Peninsula in the Far North of Russia. Statistical results of calculations of types of vegetation cover were obtained in a semi-automatic mode in ILWIS GIS. In 1988 ’willow shrubs’ type covered 412,292 pixels from the total part of the AOI, and ’high willow’ class is 823,430 pixels. 2011: willow increased to 651427 pixels, (’willow shrubs’), and 893092 pixels (’high willows’). Both combined classes of willows, typical for AOI with a high water content, cover total 1544519 pixels, which is 40.27 %. Area of grasses decreased compared to shrub and willow. Max area covered by class ’heather and dry grass’ is 933798 pixels.